Radiation, work experience, and cause specific mortality among workers at an energy research laboratory. Issue 8 (August 1985) - Checkoway, H; Mathew, R M; Shy, C M; Watson, J E; Tankersley, W G; Wolf, S H; Smith, J C; Fry, S A
Abstract : A retrospective cohort mortality study was conducted among 8375 white male employees who had worked at the Oak Ridge National Laboratory for at least one month between 1943 and 1972. This plant has been the site of energy related research, including uranium and plutonium reactor technology and radioisotope production. Radiation doses, primarily from gamma rays, were generally low; the median cumulative exposure for workers was 0.16 rems. Historical follow up was conducted for the years 1943-77 and ascertainment of vital status was achieved for 92.3% of the cohort. Standardised mortality ratios (SMRs) were computed to contrast the subjects' cause specific mortality experience with that of the United States white male population. The observed number of 966 deaths from all causes was 73% of the number expected. Mortality deficits were also seen for arteriosclerotic heart disease (SMR = 0.75; 344 observed) and all cancers (SMR = 0.78; 194 observed). These results are indicative of the healthy worker effect and the favourable influence on health of the cohort's relatively high socioeconomic status. Non-statistically significant raised SMRs were seen for all leukaemias (SMR = 1.49, 16 observed), cancer of the prostate (SMR = 1.16, 14 observed), and Hodgkin's disease (SMR = 1.10, 5 observed). Internal comparisons of mortality (standardised rate ratios, SRRs) were made between subgroups of the cohort according to radiation dose level and duration of employment in various job categories. No consistent gradients of cause specific mortality were detected for radiation exposure. Leukaemia mortality was highest among workers with greater than or equal to 10 years employment in engineering (SRR = 2.40) and maintenance (SRR = 3.12) jobs. The association of leukaemia with employment in engineering was unexpected; maintenance jobs entail potential exposures to radiation and to a wide range of organic chemicals; metals, and other substances.